Determinación del incremento de invernaderos y el cambio en la Evapotranspiración que se ha generado durante los años 2015 - 2020 mediante análisis digital de imágenes satelitales del Cantón Latacunga. Cotopaxi, Ecuador –2021 - Guanotasig Gavilema, Jordan Stalyn (2021)
The present research was conducted in the Latacunga canton, with the objective of determining the increase of greenhouses and the change in Evapotranspiration that has been generated during the years 2015 - 2020 through digital analysis of satellite images of the Latacunga Canton. The methodology used is of a documentary bibliographic level with a non-experimental research design and direct sampling; the instrument for data collection was the field trip to take the points of the greenhouses, where 20 samples were randomly chosen with the help of the geo portal of Ecuadorian agriculture that provided us with data from the greenhouses, although the dates were not updated. On the other hand, we used the website https://lpdaacsvc.cr.usgs. gov was used to download the MOD16A2 product, which contains monthly evapotranspiration information from all over the world and the monthly images were downloaded, 12 for each year of 2015 and 2020, and the USGS Earth Explorer website was used for the satellite images of 2015 and 2020, where the images with the lowest percentage of cloudiness were selected, for the corrections of radiance and reflectance of these images the ENVI software was used, Then the processing of the points, both those taken in the field and the training points, and the generation of the classes for the supervised classification was carried out with the help of the ArcGIS software, on the other hand, the process for the calculation of the evapotranspiration was carried out in the same software with the help of the Raster Calculator tool, which generates as a result a raster file with the evapotranspiration information of the study area, once the resulting data was obtained, we proceeded to the analysis where we used the Excel software for the statistical graphs. The increase of plastic coverage by greenhouses carried out through the digital analysis of satellite images of Latacunga canton was determined that it has been varying between the years 2015 and 2020 where there was an increase of 125.25% having a considerable increase of areas with plastic coverage, as for evapotranspiration there was a decrease of -29% over the five years studied and reaching the analysis that the greater the number of established greenhouses the lower the evapotranspiration emitted in the study area was lower, which was verified in the satellite images of the years studied. Therefore, the results of the research, satellite images with the help of software can be efficient and accurate alternatives for obtaining reference information as in this study was both the amount of plastic used by greenhouses and multiannual atmospheric data (evapotranspiration).